The avoidance strategy of environmental constraints by an aquatic plant Potamogeton alpinus in running waters - Robionek, Alicja (Ecol Evol, 2015)
Aquatic plants anchored in streams are under pressure from various constraints linked to the water flow and display strategies to prevent their damage or destruction. We assume that the responses of aquatic plants to fast-water flow are a manifestation of a trade-off consisting in either maximizing the resistance to damage (tolerance strategy) in minimizing the hydrodynamic forces (avoidance strategy), or both. Our main hypothesis was that Potamogeton alpinus demonstrate the avoidance strategy. We analyzed architecture traits of the modules of this clonal plant from slow- and fast-flowing streams. In fast-flowing waters, the avoidance strategy of P. alpinus is reflected by the following: (1) the presence of floating leaves that stabilize the vertical position of the stem and protect the inflorescence against immersion; (2) elongation of submerged leaves (weakens the pressure of water); and (3) shoot diameter reduction and increase in shoot density (weakens the pressure of water, increases shoot elasticity), and by contrast in slow-water flow include the following: (4) the absence of floating leaves in high intensity of light (avoiding unnecessary outlays on a redundant organ); (5) the presence of floating leaves in low intensity of light (avoidance of stress caused by an insufficient assimilation area of submerged leaves).